Total Synthesis of the Depsipeptide FR901375 and Preliminary Evaluation of Its Biological Activity. Issue 34 (7th November 2016) - Narita, Koichi; Katoh, Yuya; Ojima, Ken‐ichi; Dan, Singo; Yamori, Takao; Ito, Akihiro; Yoshida, Minoru; Katoh, Tadashi
Abstract : The bicyclic depsipeptide FR901375 was efficiently synthesized in a highly convergent manner. The synthesis involved the condensation of ad ‐valine–d ‐valine–d ‐cysteine‐containing segment with a (3 S, 4 E )‐3‐hydroxy‐7‐mercapto‐4‐heptenoic acid–l ‐threonine‐containing segment to directly assemble the corresponding seco ‐amino acid, followed by cyclization to construct the desired 16‐membered macrocyclic ring. The potency of the synthesized FR901375 was determined in assays for histone deacetylase (HDAC) inhibition and cell‐growth inhibition, and the results were compared to those obtained for the clinically approved depsipeptide FK228 (romidepsin). It was found that FR901375 shows extremely high selectivity (957‐fold) for a class I HDAC 1 (GI50 = 1.7 nm ) over a class II HDAC 6 (GI50 = 1627 nm ), and shows cell‐growth inhibition GI50 values in the low nanomolar region. Furthermore, new aspects of the structure–activity relationship of bicyclic depsipeptide HDAC inhibitors were revealed. Abstract : FR901375, a bicyclic depsipeptide natural product, was efficiently synthesized in a convergent manner. The synthesis involved amide condensation of two segments, followed by macrolactamization and disulfide bond formation. Biological evaluation revealed that FR901375 is highly selective for a class I HDAC 1 (GI50 = 1.7 nm ) over a class II HDAC 6 (GI50 = 1627 nm ) (HDAC = histone deacetylase).